KINERJA KEUANGAN DAERAH YANG DIMODERASI BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI - Linawati, Linawati; Solikah, Mar’atus (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Planned financial performance, with estimates and realization of revenues and accuracy of expenditure allocation, is expected to increase economic growth. Increased economic growth indicates increased the economic activities of that area, followed by increasing income and the welfare of its people. The financial performance is allegedly not always increasing economic growth. The purpose of this study was to analyze the effect of regional financial performance on economic growth which moderated capital expenditure in the City and Regency of the Ex-Kediri Residency. The population as well as the sample in this study are 7 regions, namely 2 cities and 5 districts in the Kediri residency of East Java. The object of research is regional financial performance, capital expenditure and economic growth. The data used is secondary data, consisting of budget data on APBD realization and economic growth, obtained from the bps and dpjk websites. Data analysis using SEM Moderating analysis. This study has found that financial performance does not have a significant and negative effect on economic growth. Capital expenditure has a significant negative effect on economic growth, and capital expenditure can be as a moderator of regional financial performance towards economic growth.